Relationship between Achilles tendon length and running performance in well‐trained male endurance runners. (19th July 2017) - Ueno, Hiromasa; Suga, Tadashi; Takao, Kenji; Tanaka, Takahiro; Misaki, Jun; Miyake, Yuto; Nagano, Akinori; Isaka, Tadao
Abstract : This study aimed to determine the relationship between Achilles tendon (AT) length and running performance, including running economy, in well‐trained endurance runners. We also examined the reasonable portion of the AT related to running performance among AT lengths measured in three different portions. The AT lengths at three portions and cross‐sectional area (CSA) of 30 endurance runners were measured using magnetic resonance imaging. Each AT length was calculated as the distance from the calcaneal tuberosity to the muscle‐tendon junction of the soleus, gastrocnemius medialis (GMAT ), and gastrocnemius lateralis, respectively. These AT lengths were normalized with shank length. The AT CSA was calculated as the average of 10, 20, and 30 mm above the distal insertion of the AT and normalized with body mass. Running economy was evaluated by measuring energy cost during three 4‐minutes submaximal treadmill running trials at 14, 16, and 18 km/h, respectively. Among three AT lengths, only a GMAT correlated significantly with personal best 5000‐m race time ( r =−.376, P =.046). Furthermore, GMAT correlated significantly with energy cost during submaximal treadmill running trials at 14 km/h and 18 km/h ( r =−.446 and −.429, respectively, P <.05 for both), and a trend toward such significance was observed at 16 km/h ( r =−.360, P =.050). In contrast, there was no correlation between AT CSA and running performance. These findings suggest that longer AT, especially GMAT, may be advantageous to achieve superior running performance, with better running economy, in endurance runners.